№1
1) (х-5)(х-8)
х1=5 х2=8
2) (2х+1)(3х-1)
х1=-0,5 х2=
№2
1) (а-1)(а-17)
2) -(х-3)(х+7)
3) 5(6у+1)(2у-1)
4) 5(3х-5)^2
№3
1) = = x-1
2) = =
4) = =
5) = =
№1
1) (х-5)(х-8)
х1=5 х2=8
2) (2х+1)(3х-1)
х1=-0,5 х2=![\frac{1}{3}](/tpl/images/1138/4165/5506e.png)
№2
1) (а-1)(а-17)
2) -(х-3)(х+7)
3) 5(6у+1)(2у-1)
4) 5(3х-5)^2
№3
1)
=
= x-1
2)
=
= ![\frac{3}{x+7}](/tpl/images/1138/4165/2667a.png)
4)
=
= ![\frac{2a+3}{a-1}](/tpl/images/1138/4165/cd34d.png)
5)
=
= ![-\frac{x+2}{x-3}](/tpl/images/1138/4165/8e043.png)